Pleiotropic Regulatory Genes as A Tool for Streptomyces Strains Bioprospecting and Improvement - Ostash, Bohdan (Current Biotechnology, 2021)
Many taxa within class Actinobacteria, most notably genus Streptomyces, are known for the abundant presence of specialized biosynthetic pathways that convert essential cellular metabolites (amino acids, acyl moieties, such as acetyl-CoA, nucleotides etc.) into diverse natural products (NPs). NPs remain one of the pillars of modern pharmaceutical industry, and use of NPs as antibiotics is perhaps the most notable example of the commercial success of NPs. Nowadays, as humankind faces a formidable challenge to counter the rise of antimicrobial resistance and viral infections, there is renewed interest in streptomycetes as a source of novel NPs. This prompted the investigation of a variety of approaches to discover novel NPs and to improve the production of known ones. The focus of this review is on the use of regulatory genes to discover novel NPs. The two-layered scheme of regulation of NP biosynthesis is described and terms referring to cryptic NP gene cluster are detailed. Major players in global regulatory network are described as well as how their manipulation may be used to access the secondary metabolomes of Streptomyces and Actinobacteria in general. The value of studying the NP regulation in the era of synthetic biology is summarized in the last section.
Keywords: Actinobacteria